A personal network approach to the study of nurse champions of innovation and their innovation projects' spread. (4th November 2020) - Luz, Shirly; Drach‐Zahavy, Anat; Shadmi, Efrat
Abstract: Aims: To develop and test the relationship between nurse champions' personal social networks and innovation success in terms of spread. Design: A cross sectional. Method(s): Data were collected on 94 nurse champions at three medium‐large tertiary medical centres from 2015–2016. Data from champions on their personal network were assessed via a standardized and acceptable three‐step network survey. Success in terms of innovation spread was assessed via perceived extent of spread. Network structural and relational characteristics were depicted by level of spread. Multivariate linear regression was used to assess the relationship between network characteristics and innovation spread. Findings: Above and beyond various project and network control variables, network density was significantly and positively related to project spread, tie‐strength diversity was significantly and negatively related to project spread and difference in ethnic origin between champions and alters was significantly and positively related to project spread. Maximum age of network members was marginally significantly related to project spread. Conclusion(s): Our findings show that high‐density personal social networks; networks where tie strength among network members is similar, thus, creating liking and trust among members; having at least one older network member who might have close access to professional and organizational resources acquired throughout their career; and having ties with network members from different ethnic groups to prevent knowledge stickiness, all promote innovation spread. Champions should be carefully nominated based on their ability to engage network members and to build ties with various network members inside and outside the nursing unit; once selected, champions should be aware of their social networks. Impact: The current study explored champions' personal‐network structure, composition and variance measures and their implications for innovation project spread. The findings demonstrated that nursing champions' personal social networks matter for innovation spread. This finding has implications for the nominating and the coaching of champions. 摘要: 目的: 发展和测试护士拥护者的个人社交网络与成功创新传播之间的关系。 设计: 横向研究。 方法: 2015年至2016年间, 我们共收集三家大中型三级医疗中心的94名护士拥护者的数据。将通过标准化、可接受的三步网络调查对拥护者的个人网络数据进行评估。创新传播的成功将可通过感知的传播程度来评估。网络的结构特征和关系特征均可通过传播水平来描述。此外, 可运用多元线性回归分析网络特征与创新传播之间的关系。 发现: 除各类项目和网络控制变量外, 网络密度与项目传播呈明显正相关, 联系强度多样性与项目传播呈明显负相关, 而拥护者和替补人员之间的种族差异与项目传播呈明显正相关。网络成员的最高龄与项目传播显著相关。 结论: 研究结果表明, 高密度的个人社交网络, 或网络成员之间联系强度相似且可用于创建联系和信任的网络, 内部都至少有一名年纪教长的网络成员, 且该成员有可能有近距离接触相关专业和组织资源;可与不同民族的网络成员建立联系, 降低知识粘性, 最终促进创新传播。拥护者的提名应以其吸引网络成员的能力以及与护理单位内外各种网络成员建立联系的能力为基础;如选中, 拥护者应了解其社交网络。 影响: 本研究探讨了拥护者的个人网络结构、构成和差异测度及其对创新项目传播的影响。研究结果表明, 护理拥护者的个人社交网络对创新传播至关重要。此研究结果对拥护者的提名和执教都有影响。